Plant community resilience in the face of fire: experimental evidence from a semi‐arid shrubland - Lipoma, Maria Lucrecia (2016)
The ability of communities or ecosystems to recover their structure and function after a disturbance is known as resilience. According to different views, resilience can be influenced by the resource-use strategies of the plantfunctional types that dominate the community or by the existence of functional redundancy within plant functional types. We investigated how the dominance of different plant functional types and species affected the resilience of amountain shrubland after an intense fire. We took advantage from a pre-existing long-term removal experiment in which either whole plant functional types (deciduous shrubs, graminoids, perennial forbs and annual forbs) or the dominantspecies within each plant functional type were removed for 10 years. We sampled species and plant functional types cover during the first growing season after the fire. First, to test whether functional redundancy increased resilience, we analyzed the existence of functional compensation inside plant functional types. Second, to test whether the dominance of plant functional types with different resource-use strategies affected recovery, we compared resilienceat the levels of species, plant functional types and total cover, estimated on the basis of a change index and multivariate Euclidean distances. No compensation was observed in any of the plant functional types. At the level of species, we found that the assemblages dominated by conservative resource-use strategies were the ones showing higher resilience.This was due to the high recovery of the dominant species of shrubs plant functional type. The opposite (lowest recovery of conservative resource-use strategies) was found at the plant functional type and total cover-levels. Our study did not support the hypothesis of resilience by functional redundancy. Instead, regeneration by buried meristems from the pre-fire stage appeared to be the factor that most influenced recovery. Resource-use strategies explained resilience of vegetation cover, but not of floristic composition. Regeneration traits, rather than vegetative traits or mechanism of functional compensation, appeared as the most relevant to explain the response of this system after fire.